THE EFFECT OF PARENTS’ ATTENTION AND LEARNING MOTIVATION TOWARDS ENGLISH SPEAKING SKILL - Dicky Hidayat Soeharyanto; Moh. Solikudin Djaelani (INFERENCE: Journal of English Language Teaching, 2018)
The purpose of this study is to learn about what concerns parents and learning motivation towards students' English language skills. If there is a positive and significant influence then make strong parents 'attention and learning motivation towards students' English skills. The research method used was a survey with a transition and regression analysis, which is connecting data that shows parents 'attention and learning motivation with data that shows students' English speaking skills. Data about the variables of parents' attention and learning motivation were obtained through a questionnaire compiled by researchers, which measures matters related to the above. While data on English speaking skills were obtained through direct tests conducted by researchers on respondents. 1) There is a significant difference with parents' attention and motivation to learn together on English speaking skills, private vocational students in Subang Regency. This is evidenced by the value of sig = 0,000 <0.05 and Fcount= 38.758. 2) There is a significant difference between parents of English speaking skills, private vocational students in Subang Regency. This is evidenced by the value of sig = 0,000 <0.05 and tcount = 5.629. 3) There are significant differences in the learning of English, students of Private Vocational Schools in Subang Regency. This is evidenced by the value of sig = 0,000 <0.05 and tcount = 3.687. Key words: Parents’ attentiom, Learning Motivation, English Speaking SkillThe purpose of this study is to learn about what concerns parents and learning motivation towards students' English language skills. If there is a positive and significant influence then make strong parents 'attention and learning motivation towards students' English skills. The research method used was a survey with a transition and regression analysis, which is connecting data that shows parents 'attention and learning motivation with data that shows students' English speaking skills. Data about the variables of parents' attention and learning motivation were obtained through a questionnaire compiled by researchers, which measures matters related to the above. While data on English speaking skills were obtained through direct tests conducted by researchers on respondents. 1) There is a significant difference with parents' attention and motivation to learn together on English speaking skills, private vocational students in Subang Regency. This is evidenced by the value of sig = 0,000 <0.05 and Fcount = 38.758. 2) There is a significant difference between parents of English speaking skills, private vocational students in Subang Regency. This is evidenced by the value of sig = 0,000 <0.05 and tcount = 5.629. 3) There are significant differences in the learning of English, students of Private Vocational Schools in Subang Regency. This is evidenced by the value of sig = 0,000 <0.05 and tcount = 3.687.Key words: Parents’ attentiom, Learning Motivation, English Speaking Skill